Digital Speech Acts on Social Media: The Content Ethnographic of Audiences Response to the Publication of Illegal Online Loans on @Ojkindonesia's Instagram Account - Rulli Nasrullah; Dewi Rahmawati Gustini (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
Social media is no longer just a channel for users to socialise with each other on the Internet but also mediates the spreading of information to applications that can be utilised in the practice of legal aspects in the economy. The character of social media, which is full of information, forms a network (networking), stores data (archive), and interactivity which is an important point in the development of legal aspects in the economy related to online loans.  Using virtual ethnography on the discourse of digital citizens in the comments column of the Financial Services Authority (OJK) Instagram account regarding  Daftar 102 Pinjaman Online Legal Berizin OJK, this study concludes that  social media is a source for users (1) to seek information;  (2) spread information;  and  (3) functiom as a centre and gateway for information that exists throughout social media users  who consciously or not have been involved as a tool of discourse among netizen in a virtual community related to legal aspects in the economy.  Information contestation cannot be avoided because, in reality, on social media, any user can produce and distribute content and have a great influence on the opinions of other users.